A checklist of the helminth parasites of invasive murid rodents in Mexico - Panti-May, Jesús Alonso; Duarte-Jiménez, Alejandra; Hernández-Batancourt, Silvia F.; Rodríguez-Vivas, Roger Iván (THERYA, 2020)
The present work provides an updated checklist of helminth species infecting invasive murid rodents (Mus musculus, Rattus norvegicus, R. rattus, and Rattus sp.) in Mexico, including 35 helminth taxa (3 trematodes, 7 cestodes, 2 acanthocephalans, and 23 nematodes). The helminthological records were compiled from 18 studies conducted in seven Mexican states up to May 2020. Information on habitats, life stages, geographical locations, hosts, helminthological collections, prevalences, and bibliographic references are included, when available. Finally, a new locality record of the nematode Hassalstrongylus musculi in Yucatan is provided.